1999
DOI: 10.1292/jvms.61.185
|View full text |Cite
|
Sign up to set email alerts
|

Amplification of the c-yes Oncogene in Canine Mammary Tumors.

Abstract: ABSTRACT. Genomic DNAs of 14 mammary tumors were analyzed by Southern blot hybridization using a human c-yes-1 oncogene probe. The amplification was successful in half of the cases (7 adenocarcinomas). The degree of amplification was approximately 4-fold, and a high proportion was seen in malignant tumors. In addition, DNA polymorphism was detected in two adenocarcinomas.-KEY WORDS: c-yes, canine, mammary tumor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2005
2005
2010
2010

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…Either the p16/INK4A and Rb pathway was defective suggesting a defect in cell cycle exit or the p53/p21 pathway was defective suggesting apoptotic signaling may be inoperative [Medema et al, 1995; Bird, 2008]. Coupled to previously identified c‐ erb B‐2 overexpression in all three cell lines and the potential for c‐ yes oncogene activation in such canine tumors, we have proposed a putative model for spontaneous canine mammary cancer [Miyoshi et al, 1991; Ahern et al, 1996; Rungsipipat et al, 1999; Bird, 2008]. Such detailed genetic characterization places these cell lines and canine mammary cancers as highly comparable intermediate models between murine and human breast cancers (Table I).…”
Section: Discussionmentioning
confidence: 66%
“…Either the p16/INK4A and Rb pathway was defective suggesting a defect in cell cycle exit or the p53/p21 pathway was defective suggesting apoptotic signaling may be inoperative [Medema et al, 1995; Bird, 2008]. Coupled to previously identified c‐ erb B‐2 overexpression in all three cell lines and the potential for c‐ yes oncogene activation in such canine tumors, we have proposed a putative model for spontaneous canine mammary cancer [Miyoshi et al, 1991; Ahern et al, 1996; Rungsipipat et al, 1999; Bird, 2008]. Such detailed genetic characterization places these cell lines and canine mammary cancers as highly comparable intermediate models between murine and human breast cancers (Table I).…”
Section: Discussionmentioning
confidence: 66%
“…Canine studies have shown increased levels of both the protein and mRNA of c-erbB-2 in malignant but not in normal or benign tissues(Ahern et al 1996;Dutra et al 2004;Rungsipipat et al 1999a). The human oncogenes COX-2 and c-yes-1 have also been documented to be aberrantly expressed in canine mammary cancers(Dore et al 2003;Heller et al 2005;Miyoshi et al 1991;Queiroga et al 2005a;Rungsipipat et al 1999a;Rungsipipat et al 1999b). Four heat shock proteins (Hsp27, Hsp72, Hsp73, and Hsp90) were analyzed using canine mammary tissue from 3 normals and 30 malignant cases(Romanucci et al 2006).…”
mentioning
confidence: 99%
“…(C) In vitro transcribed 32 P-labeled RNA probes (ARE II-III) were incubated with recombinant purified p38 AUF1 (rAUF1) in the presence or absence of a 1000-fold molar excess of a non-specific (ns) or a specific (s) cold competitor RNA. carcinoma, and a broad range of human cancers, such as colon, breast, head and neck, renal, lung, and stomach cancer [38][39][40].…”
Section: Discussionmentioning
confidence: 99%